50 years Institute for Nuclear Research: exploring the high-energy universe. (1st March 2022) - Spiering, C
Abstract: This article is an attempt to review 50 years of high-energy cosmic particle physics at the Institute for Nuclear Research of the Russian Academy of Sciences. It is written by an outsider whose scientific career, to a large part, was shaped by collaborating with INR scientists in the late 1980s and 1990s. The review covers the fields of cosmic-ray, gamma-ray, and high-energy neutrino physics. The main focus will be on INR's large facilities in the Baksan Valley and at Lake Baikal. Research at these facilities is accompanied by participation in top experiments at different places around the world: recently, the Telescope Array in the USA and the LHAASO detector in China.